фольклорно-етнографічні матеріали на сторінках журналу «Основа» - Чибирак, С. (Народна творчість та етнографія, 2009)
In the article folk and ethnographical materials of the «Osnova» magazine are analyzed. The role of this edition in development of the ethnography is defined.